The psichopolitical emancipation against the epistemic trauma and the communication theory - Vieira Ouriques, Evandro (2016)
This article describes how the epistemic constitution of the theory of communication depends on critical thinking understands that emancipation is an unfolding of overcoming the epistemic trauma of dualism, which is the basis of the psichopolitical perspective in the theory. Such a trauma tends to be embodied and embedded in an hegemonic way in the mental territory of philosopher, social scientist, the communications expert and the activist, and, generally, in the sciences, the arts and the individuals of central societies of globalization and those settled on dualism, which is expressed in a theoretical, methodological and experiential way.